Evaluation of Freestyle Optium Neo H andTaiDoc‐TD4235 point‐of‐care meters for measuring blood β‐hydroxybutyrate concentration in sheep - Tümer, Kenan C.; Kılınç, Mehmet A. (Wiley, 2023)
AbstractBackgroundAccurate and rapid measurement of blood β‐hydroxybutyrate (β‐OHB) concentrations is critical to identify hyperketonemia in sheep.ObjectiveThe objective of this study was to test the performance of Freestyle Optium Neo H and TaiDoc‐TD4235 point‐of‐care (POC) devices for measuring blood β‐OHB concentrations in sheep.MethodsVenous blood samples from 105 sheep were evaluated with Freestyle Optium Neo H and TaiDoc‐TD4235 meters. A reference approach was the laboratory measurement of serum BHB concentrations using the Randox D‐3 Hydroxybutyrate reagent kit. Data were analyzed using Passing‐ Bablok regression and Bland–Altman analysis. The diagnostic accuracy was assessed using serum β‐OHB concentration at a cut‐off value of 0.8 mmol/L.ResultsPassing‐Bablok regression analysis revealed an intercept of 0.066 (CI95: 0.018–0.125) and slope of 1.242 (CI95: 1.136–1.342) for Freestyle Optium Neo H. Intercept and slope values for the TaiDoc‐TD4235 meter were 0.625 (CI95: 0.539–0.724) and 1.265 (CI95: 1.044–1.497), respectively. The Bland–Altman plot revealed a bias of 0.224 mmol/L and 0.737 mmol/L for Freestyle Optium Neo H and TaiDoc‐TD4235 meters, respectively, compared with the reference method. Observed Total Error (TEobs) was 56.7% for the Freestyle Optium Neo H and 168.7% for the Taidoc‐TD4235. The sensitivity and specificity for the Freestyle Optium Neo H were 100% and 80.9%, respectively, at the threshold of 0.8 mmol/L. The Taidoc‐TD4235 demonstrated a sensitivity of 93.3% and specificity of 8.9% at the threshold of 0.8 mmol/L.ConclusionsBecause of the large TEobs, the Freestyle Optium Neo H and TaiDoc‐TD4235 meters should not be used to quantify blood β‐OHB concentrations in sheep.
Keywords: Blood Glucose; Sheep; Hydroxybutyric Acid; Point-of-Care Systems; Animals; Sheep Diseases; Ketosis; Sensitivity and Specificity